A new professional figure: The specialist teacher of primary physical education - Francesco Casolo; Ilaria Tosi (Pensa MultiMedia, 2023)
After more than 40 years, the inclusion of a Motor and Sport Science graduate in primary school has become a reality. Articles 1(329-340) of the Italian Law 234/2021 is the result of an innovative and cultural choice promoted by the Italian policy makers. Specifically, it involves the implementation and inclusion of the specialist teacher (i.e., disciplinary) along with the non-specialized teacher (i.e., generalist) in the context of the teaching of primary physical education. This new professional figure will contribute to enrich primary education by enhancing children's motor, interpersonal and intrapersonal intelligence. A high-quality education and training to these novel reference figures should be granted. Accordingly, universities should ensure in bachelor's and master's degree programs related to Motor and Sport Sciences, an appropriate number of credits to be reserved for the training of those specific skills demanded for a high-quality physical education teaching.